2008
DOI: 10.1164/rccm.200712-1869oc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pharmacotherapy on Rate of Decline of Lung Function in Chronic Obstructive Pulmonary Disease

Abstract: Pharmacotherapy with salmeterol plus fluticasone propionate, or the components, reduces the rate of decline of FEV(1) in patients with moderate-to-severe COPD, thus slowing disease progression. Clinical trial (GSK Study Code SCO30003) registered with www.clinicaltrials.gov (NCT00268216).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
463
6
45

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 701 publications
(534 citation statements)
references
References 40 publications
20
463
6
45
Order By: Relevance
“…In the TORCH study, the combination of ICS and LABA reduced the rate of decline in FEV 1 in patients with moderate-to-severe COPD by 16 ml/year compared to placebo. This improvement was also observed in the LABA-only and in the ICS-only group [152].…”
Section: Combination Of Ics With Labasupporting
confidence: 65%
See 1 more Smart Citation
“…In the TORCH study, the combination of ICS and LABA reduced the rate of decline in FEV 1 in patients with moderate-to-severe COPD by 16 ml/year compared to placebo. This improvement was also observed in the LABA-only and in the ICS-only group [152].…”
Section: Combination Of Ics With Labasupporting
confidence: 65%
“…However, in two subsequent meta-analyses published, one concluded that ICS reduced FEV 1 decline by a small statistical mean rate of 7.7 ml/year [150], while another meta-analysis showed a non-significant 5.0 ml/year reduction [151]. However, in the 3-year TORCH study, a multicentre double-blind placebo-controlled randomised clinical trial involving 6,112 patients with COPD (mean post-bronchodilator FEV1 of 44%), fluticasone showed a significant improvement in FEV 1 decline of −42 ml/year compared to placebo of −55 ml/year [152]. This effect was not significantly different from that of salmeterol or of the combination of salmeterol and fluticasone together.…”
Section: Effect Of Ics Alonementioning
confidence: 95%
“…Not fully, since treatment may reduce the number of exacerbations but not necessarily affect lung function decline in the same patient. In addition, even if this is the case in a subset of COPD patients, 7,8 it is not clear which characteristics predict this response. This also holds true for mortality as a future risk: here we have information that a composite measure such as the BODE index predicts mortality better than airflow obstruction alone and at the same time predicts future exacerbations.…”
Section: Exacerbations As An Example Of the Link Between Best Currentmentioning
confidence: 99%
“…PRIMARY CARE RESPIRATORY JOURNAL www.thepcrj.org data support the efficacy of existing pharmacological treatments on prevention of exacerbations, 5,6 together with some effect on lung function decline 7,8 and improved survival, 9 many clinicians remain sceptical. Additionally, non-pharmacological treatment options in secondary care -including pulmonary rehabilitation, lung volume reduction surgery, oxygen therapy and influenza vaccination -have successfully improved well-being and/or the prognosis of COPD, but are often not considered.…”
mentioning
confidence: 93%
“…15,16 Improving patients' ability to use inhalers may help prevent adverse events post-hospital discharge, including hospital readmissions. [17][18][19] Although a handful of randomized trials have demonstrated beneficial effects of hospital-based patient selfmanagement education for asthma, [20][21][22][23] these studies employed multi-faceted, time-intensive interventions that were compared to usual care. While this literature encourages the use of hospital-based education, direction is lacking as to which intervention or component is most effective.…”
Section: Introductionmentioning
confidence: 99%